Finance for growth : policy choices in a volatile world. - Caprio, Gerard (World Bank policy research report., 2001)
The overall impact of financial globalization on the domestic financial sector is profound. Liberalization of capital flows has effectively made domestic financial repression obsolete. The consequences have not been uniformly favorable. Following liberalization, domestic interest rates in developing countries have moved to a premium over industrial country rates, and can surge at times of currency speculation. Heightened interest rate and exchange rate volatility pose practical risk management difficulties for financial intermediaries and reinforce the need for appropriate infrastructures and incentives for risk containment, as well as for good macropolicies. On the other hand, the cost of equity capital has been reduced by allowing foreign investor access to local equity markets and allowing local firms to list abroad. Increased international flows through the equity markets have not been the major contributor to increased international sources of volatility. In addition to opening access to foreign-sourced financial services, more and more countries have been permitting foreign-owned banks and other financial firms to operate locally. Although this can represent a threat to domestic owners of financial firms, the drawback is outweighed by improved service quality. On all three fronts--debt, equity, and services--the costs and risks as well as the benefits of increased financial globalization. knowledges.